1950
DOI: 10.1172/jci102267
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Diuretics. I. The Site of Action of Mercurial Diuretics 1

Abstract: Although it is generally accepted that organic mercurial diuretics depress the renal tubular absorption of sodium,2 precise localization of their site of action within the tubule has not been accomplished. If one administers graded doses of such diuretics to the dog it becomes apparent that, above a certain level, further increases in dosage yield progressively diminishing increments of sodium excretion. This pattern of response suggests that these agents depress some specific fraction of total sodium absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1950
1950
1965
1965

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Duggan and Pitts (27) recently have concluded that in dogs mercurials act by depressing distal tubular reabsorption of electrolytes and water. This conclusion was based chiefly on the fact that despite massive doses of mercurials, the sodium excreted never exceeded 21 %o of that filtered, whereas, 67%o to 87%o of filtered sodium is generally considered to be reabsorbed proximally.…”
Section: Discussionmentioning
confidence: 99%
“…Duggan and Pitts (27) recently have concluded that in dogs mercurials act by depressing distal tubular reabsorption of electrolytes and water. This conclusion was based chiefly on the fact that despite massive doses of mercurials, the sodium excreted never exceeded 21 %o of that filtered, whereas, 67%o to 87%o of filtered sodium is generally considered to be reabsorbed proximally.…”
Section: Discussionmentioning
confidence: 99%
“…After two control periods 160 mg. of mercury as mercuhydrin were administered intravenously. The high rate of infusion of saline protects the animal against the acute circulatory collapse which often follows large doses of mercurial diuretics and also produces a prolonged, sustained mercurial diuresis (15). Phosphate was given to stabilize urine pH and to avoid the disturbing fluctuations often ob- served when the urine is poorly buffered.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some investigators concluded that the distal tubule represented the site of mercurial action because the magnitude of the diuresis approximated the quantity of salt and water normally absorbed within the distal tubule (13). Others, who observed that the rate of excretion of * Supported by a grant from the National Institute of Arthritis and Metabolic Diseases, National Institutes of Health (Grant no.…”
mentioning
confidence: 99%